A New Framework for Understanding Inequalities Between Expatriates and Host Country Nationals - Oltra, Victor (Journal of business ethics, 2013)
An interdisciplinary theoretical framework is proposed for analysing justice in global working conditions. In addition to gender and race as popular criteria to identify disadvantaged groups in organizations, in multinational corporations (MNCs) local employees (i.e. host country nationals (HCNs) working in foreign subsidiaries) deserve special attention. Their working conditions are often substantially worse than those of expatriates (i.e. parent country nationals temporarily assigned to a foreign subsidiary). Although a number of reasons have been put forward to justify such inequalities—usually with efficiency goals in mind—recent studies have used equity theory to question the extent to which they are perceived as fair by HCNs. However, since perceptual equity theory has limitations, this study develops an alternative and non-perceptual framework for analysing such inequalities. Employment discrimination theory and elements of Rawls’s ‘Theory of Justice’ are the theoretical pillars of this framework. This article discusses the advantages of this approach for MNCs and identifies some expatriation practices that are fair according to our non-perceptual justice standards, whilst also reasonably (if not highly) efficient.